2018
DOI: 10.1039/c8cc02760a
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of full-length P450BM3 with an artificial metal complex by utilising the transpeptidase Sortase A

Abstract: Haem substitution is an effective approach to tweak the function of haemoproteins. Herein, we report a facile haem substitution method for self-sufficient cytochrome P450BM3 (CYP102A1) from Bacillus megaterium utilising the transpeptidase Sortase A from Staphylococcus aureus. We successfully constructed Mn-substituted BM3 and investigated its catalytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 27 publications
2
15
0
2
Order By: Relevance
“…In recent years, the chemical repertoire of P450BM3 has grown to encompass non‐natural carbene and nitrene insertions, leading to the development of a specialised mutant library, such as the carbene transferase, P411‐HF . Aside from mutagenesis, exchange of the iron protoporphyrin IX (haem) prosthetic group for artificial metalloporphyrins has also been conducted as a way to further tune the reactivity and stereoselectivity of metalloproteins . As an alternative approach, our group has reported the use of decoy molecules as a means to compel wild‐type P450BM3 into hydroxylating non‐native substrates .…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…In recent years, the chemical repertoire of P450BM3 has grown to encompass non‐natural carbene and nitrene insertions, leading to the development of a specialised mutant library, such as the carbene transferase, P411‐HF . Aside from mutagenesis, exchange of the iron protoporphyrin IX (haem) prosthetic group for artificial metalloporphyrins has also been conducted as a way to further tune the reactivity and stereoselectivity of metalloproteins . As an alternative approach, our group has reported the use of decoy molecules as a means to compel wild‐type P450BM3 into hydroxylating non‐native substrates .…”
Section: Introductionsupporting
confidence: 58%
“…Although reports describing the reconstitution of P450BM3 with artificial cofactors (aluminium protoporphyrin IX, iron(III) deuteroporphyrin IX, and methyliridium deuteroporphyrin IX) do exist, there is a lack of P450BM3 crystal structures containing artificial cofactors, and, until recently, only the crystal structure of mutant P450BM3 with iron(III) deuteroporphyrin IX had been reported on the PDB (PDB ID: 5JQU and 5JQV) . Recently, our group reported the crystal structure of the P450BM3 haem domain incorporating manganese protoporphyrin IX (MnPPIX), at a mediocre resolution of 3.10 Å (PDB ID: 5ZIS), which, although sufficient to indicate the correct reconstitution of P450BM3 with MnPPIX, was insufficient to allow the discussion of structural perturbations of the side chains. To highlight the superiority of the batch‐microcrystallisation method using seeds of P450BM3–AbiATrp, we endeavoured to crystallise the P450BM3 haem domain after reconstitution with a selection of d‐block transition metals of the periods 4 (Cr, Mn, Co) and 5 (Mo, Ru, Rh).…”
Section: Resultsmentioning
confidence: 99%
“…In den letzten Jahren erweiterte sich das chemische Repertoire von P450BM3 um unnatürliche Carben‐ und Nitreneinführungen, was zur Entwicklung einer spezialisierten Mutantenbibliothek führte, wie beispielsweise die Carbentransferase P411‐HF . Abgesehen von der Mutagenese wurde auch der Austausch der Eisenprotoporphyrin‐IX‐prosthetischen Gruppe (Häm) gegen künstliche Metalloporphyrine als Mittel zur weiteren Einstellung der Reaktivität und Stereoselektivität von Metalloproteinen durchgeführt . Als alternative Herangehensweise hat unsere Gruppe bereits die Verwendung von Täuschmolekülen als Hilfsmittel berichtet, um Wildtyp‐P450BM3 zur Hydroxylierung nichtnativer Substrate zu treiben .…”
Section: Introductionunclassified
“…In the case of the archetypical cytochrome P450 BM3 enzyme, the heme domain is fused to its redox partners in a single polypeptide chain which leads to the highest catalytic activity observed among the cytochrome P450 superfamily [8]. Several approaches have been utilized to develop fusion proteins to emulate the single polypeptide chain in P450 BM3 [9][10][11]. In addition, Munro and coworkers elegantly showed that the P450 BM3 holoenzyme acts as dimers in solution [12].…”
Section: Introductionmentioning
confidence: 99%